Access to Justice for Gig Workers: Contrasting Answers from Canadian and American Courts - Coiquaud, Urwana; Martin, Isabelle (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2020)
With the introduction of digital platforms in the Canadian labour law’s landscape comes an increased used of agreements imposing arbitration as a dispute resolution mechanism. To challenge their classification as independent workers and gain employment standards acts’ protection, gig workers therefore need to submit their disputes to a private proceeding, often located outside Canada. It is in this context that the Ontario Court of Appeal’s decision to invalidate the arbitration clause in Hellerv Uber Technologies Inc. must be read. Having granted leave for appeal, will the Supreme Court of Canada follow in the footsteps of American law and allow mandatory arbitration agreements to impede collective actions challenging the misclassification of gig workers? Our study of the Ontarian and American decisions regarding the validity of mandatory arbitration agreements between Uber and its drivers brings to light the determining impact of the approach chosen by courts.